High-nickel positive electrode material, preparation method thereof, positive electrode sheet and battery

CN122907607APending Publication Date: 2026-10-13NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610856144.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-12
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而这都未从源头解决界面氧化活性较高以及包覆层可能阻碍离子传输导致动力学较差的问题

Benefits of technology

[0029]本申请提供的一种高镍正极材料及其制备方法、正极片和电池,通过设定内层区域部内的锂镍混排率高于外层区域部内的锂镍混排率;内层区域部内的锰元素的摩尔百分比低于外层区域部内的锰元素的摩尔百分比。如此设置,使得锂层中Ni2+的含量提高后,为保持整个高镍正极材料的电中性,过渡金属层中Ni价态会降低;和锂镍混排率比较均一的高镍正极材料相比,在容量相似的情况下,本申请的内层区域部内的锂镍混排率高于外层区域部内的锂镍混排率的设置有效降低了材料在满充态下体相中的活性Ni4+浓度,从而从热力学源头抑制正极材料的界面氧化活性。并且,由于Mn一般以四价存在于正极材料中,在循环过程中并不参与氧化还原,故外层区域部中的多的Mn4+的浓度可以支撑正极材料结构。另外,由于外层区域部的电荷守恒,外层区域部内的Mn4+的浓度高,可以降低外层区域部内的镍的价态。因此,Mn4+的浓度呈现出外层区域部大于内层区域部的设定,也可以降低正极材料内镍的价态,故而也能抑制正极材料的界面氧化活性。最后外层区域部内由于具有低于内层区域部的锂镍混排度,并富含可以稳定结构的Mn4+,外层区域部的低混排保证了锂离子扩散通道的畅通,补偿内层区域部的动力学损失,可以保证正极材料的离子电导率。综上,内层区域部内的锂镍混排率高于外层区域部内的锂镍混排率和内层区域部内的锰元素的摩尔百分比低于外层区域部内的锰元素的摩尔百分比都抑制了高镍正极材料的Ni平均价态,从而从热力学源头抑制正极材料的界面氧化活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907607A_ABST
    Figure CN122907607A_ABST
Patent Text Reader

Abstract

The application provides a high-nickel positive electrode material, a preparation method of the high-nickel positive electrode material, a positive electrode sheet and a battery. The chemical formula of the high-nickel positive electrode material comprises Li 1‑x Ni a Co b Mn c O2. The high-nickel positive electrode material comprises an inner layer region and an outer layer region. The outer layer region is coated on the outer surface of the inner layer region. The lithium-nickel mixing rate in the inner layer region is higher than that in the outer layer region. The lithium-nickel mixing rate is the proportion of Ni atoms occupying Li sites. The molar percentage of manganese elements in the inner layer region is lower than that in the outer layer region. The inner layer region is formed in the region from the geometric center of the high-nickel positive electrode material to R / 2. The outer layer region is formed in the region from R / 2 to R. R is the radius of the high-nickel positive electrode material. The high-nickel positive electrode material can inhibit the interface oxidation activity of the high-nickel positive electrode material on the basis of ensuring the ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a high-nickel cathode material and its preparation method, cathode sheet and battery. Background Technology

[0002] With the rapid development of new energy vehicles, energy storage systems and consumer electronics, higher requirements have been placed on the energy density, cycle life and compaction density of batteries.

[0003] High-nickel cathode materials (such as LiNi) x Co y Mn₂O₂ (x≥0.6) is a key cathode material for next-generation high-energy-density lithium-ion batteries. However, when the charging voltage is increased to 4.4V and above, the material faces two coupled failure mechanisms: lattice oxygen instability and release of reactive oxygen species at high potentials, and high oxidation state (Ni) 4+ Both have high oxidizing activity and can induce violent redox reactions in the electrolyte, leading to gas production (especially CO2), interface deterioration, and capacity decay.

[0004] Existing technologies typically employ metal doping to improve structural stability and kinetics, and uniform surface coating to physically isolate the electrolyte. However, these methods do not fundamentally address the issues of high interfacial oxidation activity and the potential for the coating layer to impede ion transport, leading to poor kinetics.

[0005] Therefore, how to suppress the interfacial oxidation activity of high-nickel cathode materials while ensuring ionic conductivity is an urgent technical challenge that needs to be solved. Summary of the Invention

[0006] This application provides a high-nickel cathode material and its preparation method, cathode sheet, and battery, which can suppress the interfacial oxidation activity of the high-nickel cathode material while ensuring ionic conductivity.

[0007] Firstly, this application provides a high-nickel cathode material, the chemical formula of which includes Li 1- x Ni a Co b Mn c O2, where 0.01≤x≤0.05, 0.55≤a≤0.9, 0≤b≤0.2, 0≤c≤0.4, 2.1≤2a+3b+4c≤2.85;

[0008] The high-nickel cathode material includes an inner layer region and an outer layer region, the outer layer region covering the outer surface of the inner layer region, and the lithium-nickel mixing ratio in the inner layer region is higher than that in the outer layer region; wherein, the lithium-nickel mixing ratio is the proportion of Ni atoms occupying Li sites;

[0009] The molar percentage of manganese element in the inner region part is lower than the molar percentage of manganese element in the outer region part; the molar percentage of manganese element in the inner region part is the percentage of the molar amount of manganese element in the inner region part accounting for the total molar amount of nickel element, cobalt element and manganese element in the high-nickel positive electrode material; the molar percentage of manganese element in the outer region part is the percentage of the molar amount of manganese element in the outer region part accounting for the total molar amount of nickel element, cobalt element and manganese element in the high-nickel positive electrode material;

[0010] The inner region part is a region formed within the range from the geometric center of the high-nickel positive electrode material to R / 2; the outer region part is a region formed within the range from R / 2 to R; wherein R is the radius of the high-nickel positive electrode material.

[0011] In a possible implementation, the surface of the high-nickel positive electrode material is coated with an amorphous rock-salt phase layer;

[0012] The chemical formula of the amorphous rock-salt phase layer includes Li 1+y M d Mn e O Z , where 0.2<d<0.6, 0.2<e<0.6, 0<y<0.4, M includes at least one element selected from Nb, Ti, Ta and Mo, and 1+y+d*(valence state of M element)+e*3=2Z.

[0013] In a possible implementation, the lithium-nickel anti-site disorder rate in the inner region part is 2%-5%; the lithium-nickel anti-site disorder rate in the outer region part is less than 2%.

[0014] In a possible implementation, the absolute value of the difference between the molar percentage of manganese element in the inner region part and the molar percentage of manganese element in the outer region part is 1%-6%.

[0015] In a possible implementation, along the direction from the inner region part to the outer region part of the high-nickel positive electrode material, the molar percentage of manganese element in the outer region part increases in a gradient manner.

[0016] In a possible implementation, the thickness of the amorphous rock-salt phase layer is 20nm-40nm.

[0017] In a second aspect, the present application provides a preparation method of the above high-nickel positive electrode material, and the method comprises:

[0018] S1: Mix deionized water, ammonia water and an alkali solution to form a base solution, add mixed solution A to the base solution for reaction, so as to obtain reactant I; wherein the mixed solution A includes a nickel salt solution, a cobalt salt solution and a manganese salt solution;

[0019] S2: Ammonia water, alkaline solution and mixed solution C are passed into reactant I and reacted, then dried to obtain the first intermediate product; wherein, the mixed solution C includes nickel salt solution, cobalt salt solution and manganese salt solution, and the molar percentage of manganese in the mixed solution C is greater than the molar percentage of manganese in the mixed solution A;

[0020] S3: The first intermediate product and the lithium source are mixed and sintered for the first time to obtain the high-nickel cathode material; wherein the amount of lithium source and the first intermediate product added satisfies the molar ratio of Li / (Ni+Co+Mn) as (0.98-1.06):1.

[0021] In one possible implementation, the first sintering is carried out in an oxygen-containing atmosphere, the temperature of the first sintering is 700-900°C, and the time of the first sintering is 10-20 hours.

[0022] In one possible implementation, S3 includes:

[0023] S31: The first intermediate product is impregnated in the mixed solution D and dried to obtain the second intermediate product; wherein, the mixed solution D includes a complexing agent solution, a manganese salt solution, a salt solution containing element M and a lithium source, and M includes at least one element selected from Nb, Ti, Ta and Mo;

[0024] S32: The second intermediate product and the lithium source are mixed and subjected to a second sintering to obtain the high-nickel cathode material; wherein the amount of lithium source and the second intermediate product added satisfies the molar ratio of Li / (Ni+Co+Mn) as (0.98-1.06):1;

[0025] The second sintering includes a first-stage sintering and a second-stage sintering. The first-stage sintering is carried out in an inert atmosphere at a temperature of 400-600℃ for 3-5 hours. The second-stage sintering is carried out in an oxygen-containing atmosphere at a temperature of 700-900℃ for 10-20 hours.

[0026] In one possible implementation, the mixed solution C comprises a mixed solution A1 and a solution B. Mixed solution A1 comprises a nickel salt solution, a cobalt salt solution, and a manganese salt solution. Solution B comprises a manganese salt solution. During the reaction of mixed solution C with reactant I, the flow rate of solution B in mixed solution C is increased at set intervals; the set interval is 1-3 hours. The molar percentage of manganese in mixed solution C is a, and the molar percentage of manganese in mixed solution A is b, where 0%... <a-b≤10%。

[0027] Thirdly, this application provides a positive electrode sheet, including the aforementioned high-nickel positive electrode material.

[0028] Fourthly, this application provides a battery including the aforementioned positive electrode.

[0029] This application provides a high-nickel cathode material, its preparation method, cathode sheet, and battery. The lithium-nickel mixing ratio in the inner layer is set to be higher than that in the outer layer; the molar percentage of manganese in the inner layer is lower than that in the outer layer. This configuration ensures that the Ni content in the lithium layer... 2+ With the increased content of Ni, the valence state of Ni in the transition metal layer will decrease in order to maintain the overall electroneutrality of the high-nickel cathode material. Compared with high-nickel cathode materials with relatively uniform lithium-nickel mixing ratio, under similar capacity conditions, the setting of a higher lithium-nickel mixing ratio in the inner layer region than in the outer layer region in this application effectively reduces the active Ni in the bulk phase of the material in the fully charged state. 4+ The concentration of Mn is thus reduced, thereby suppressing the interfacial oxidation activity of the cathode material from a thermodynamic source. Furthermore, since Mn generally exists in the cathode material in a tetravalent state and does not participate in redox reactions during cycling, the excess Mn in the outer region... 4+ The concentration of Mn in the outer region can support the cathode material structure. Furthermore, due to charge conservation in the outer region, the Mn content in the outer region... 4+ A high concentration of Mn can lower the valence state of nickel in the outer layer region. Therefore, Mn 4+ The concentration of nickel in the outer layer is set higher than that in the inner layer, which can reduce the valence state of nickel in the cathode material and thus suppress the interfacial oxidation activity of the cathode material. Finally, the outer layer has a lower lithium-nickel mixing degree than the inner layer and is rich in Mn, which can stabilize the structure. 4+ The low mixing ratio in the outer region ensures unobstructed lithium-ion diffusion channels, compensating for the kinetic losses in the inner region and maintaining the ionic conductivity of the cathode material. In summary, the higher lithium-nickel mixing ratio in the inner region compared to the outer region, and the lower molar percentage of manganese in the inner region compared to the outer region, both suppress the average Ni valence state in the high-nickel cathode material, thereby inhibiting interfacial oxidation activity at the thermodynamic source. Attached Figure Description

[0030] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0031] Figure 1 EPMA diagram of the high-nickel cathode material of Example 1 provided in this application;

[0032] Figure 2 for Figure 1 The Mn element concentration distribution map scanned along the red line of the cross section;

[0033] Figure 3 XPS valence state test images of the high-nickel cathode material surfaces of Examples 1, 1, and 2 provided in this application;

[0034] Figure 4 TEM image of the high-nickel cathode material of Example 1 provided in this application;

[0035] Figure 5 The DQ / DV curves of the battery formation process of Embodiment 1, Comparative Examples 1 and 2 provided in this application;

[0036] Figure 6 FIB-TEM image of the inner layer region of the high-nickel cathode material of Example 1 provided in this application.

[0037] The accompanying drawings illustrate specific embodiments of this application, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the concept in any way, but rather to illustrate the concept of this application to those skilled in the art through reference to particular embodiments. Detailed Implementation

[0038] To enable those skilled in the art to better understand the present invention, this application will be further described in detail below. The specific embodiments listed below are merely descriptions of the principles and features of the present invention, and the examples are only for explaining the invention and are not intended to limit its scope. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. When the following description relates to the accompanying drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements.

[0039] Firstly, this application provides a high-nickel cathode material, the chemical formula of which includes Li 1- x Ni a Co b Mn c O2, where 0.01≤x≤0.05, 0.55≤a≤0.9, 0≤b≤0.2, 0≤c≤0.4, 2.1≤2a+3b+4c≤2.85;

[0040] The high-nickel cathode material includes an inner layer region and an outer layer region. The outer layer region covers the outer surface of the inner layer region. The lithium-nickel mixing ratio in the inner layer region is higher than that in the outer layer region. The lithium-nickel mixing ratio is the proportion of Ni atoms occupying Li sites.

[0041] The molar percentage of manganese in the inner layer is lower than that in the outer layer; the molar percentage of manganese in the inner layer is the percentage of the molar amount of manganese in the inner layer relative to the total molar amount of nickel, cobalt, and manganese in the high-nickel cathode material; the molar percentage of manganese in the outer layer is the percentage of the molar amount of manganese in the outer layer relative to the total molar amount of nickel, cobalt, and manganese in the high-nickel cathode material.

[0042] The inner region is the area formed from the geometric center of the high-nickel cathode material to R / 2; the outer region is the area formed from R / 2 to R; where R is the radius of the high-nickel cathode material.

[0043] Specifically, it should be noted that the actual high-nickel cathode material has a spherical structure, so R is actually the equivalent radius of the high-nickel cathode material.

[0044] This application provides a high-nickel cathode material, its preparation method, cathode sheet, and battery. The lithium-nickel mixing ratio in the inner layer is set to be higher than that in the outer layer; the molar percentage of manganese in the inner layer is lower than that in the outer layer. This configuration ensures that the Ni content in the lithium layer... 2+ With the increased content of Ni, the valence state of Ni in the transition metal layer will decrease in order to maintain the overall electroneutrality of the high-nickel cathode material. Compared with high-nickel cathode materials with relatively uniform lithium-nickel mixing ratio, under similar capacity conditions, the setting of a higher lithium-nickel mixing ratio in the inner layer region than in the outer layer region in this application effectively reduces the active Ni in the bulk phase of the material in the fully charged state. 4+ The concentration of Mn is thus reduced, thereby suppressing the interfacial oxidation activity of the cathode material from a thermodynamic source. Furthermore, since Mn generally exists in the cathode material in a tetravalent state and does not participate in redox reactions during cycling, the excess Mn in the outer region... 4+ The concentration of Mn in the outer region can support the cathode material structure. Furthermore, due to charge conservation in the outer region, the Mn content in the outer region... 4+ A high concentration of Mn can lower the valence state of nickel in the outer layer region. Therefore, Mn 4+ The concentration of nickel in the outer layer is set higher than that in the inner layer, which can reduce the valence state of nickel in the cathode material and thus suppress the interfacial oxidation activity of the cathode material. Finally, the outer layer has a lower lithium-nickel mixing degree than the inner layer and is rich in Mn, which can stabilize the structure. 4+The low cation mixing in the outer region portion ensures unobstructed lithium ion diffusion channels, compensates for the kinetic loss in the inner region portion, and can guarantee the ionic conductivity of the positive electrode material. In summary, both the fact that the lithium-nickel cation mixing ratio in the inner region portion is higher than that in the outer region portion and the fact that the molar percentage of manganese element in the inner region portion is lower than that in the outer region portion suppress the average Ni valence state of the high-nickel positive electrode material, thereby inhibiting the interfacial oxidation activity of the positive electrode material from the thermodynamic source.

[0045] It can be understood that 0.01≤x≤0.05, for example 0.01, 0.02, 0.04, 0.05 or a range formed by any two of them.

[0046] It can be understood that 0.55≤a≤0.9, for example 0.55, 0.6, 0.7, 0.8, 0.9 or a range formed by any two of them.

[0047] It can be understood that 0≤b≤0.2, for example 0, 0.1, 0.2 or a range formed by any two of them.

[0048] It can be understood that 0≤c≤0.4, for example 0, 0.1, 0.2, 0.3, 0.4 or a range formed by any two of them.

[0049] It can be understood that 2.1≤2a+3b+4c≤2.85, for example 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.85 or a range formed by any two of them.

[0050] In a possible embodiment, the surface of the high-nickel positive electrode material is coated with an amorphous rock-salt phase layer; the chemical formula of the amorphous rock-salt phase layer includes Li 1+y M d Mn e O Z wherein 0.2<d<0.6, 0.2<e<0.6, 0<y<0.4, M comprises at least one element selected from Nb, Ti, Ta and Mo, and 1+y+d*(valence state of M element)+e*3=2Z.

[0051] The surface of the high-nickel positive electrode material of the present application is coated with an amorphous rock-salt phase layer. This layer has a disordered rock-salt phase structure, which itself has good lithium ion conductivity and structural stability, and can inhibit the formation of degraded NiO rock-salt phase.

[0052] In addition, the outer interface layer of the high-nickel positive electrode material will cause the positive electrode material to form different side reactants, affect the gas consumption reaction at the negative electrode, and ultimately affect the gas production of the overall material. Generally, the oxidative gas production of the uncoated positive electrode material is much higher than that of the material coated with multiple elements, but as time continues to extend, the actual gas production in the later stage shows little difference. The actual reason is that the side reaction induced by the coating material will instead lead to the accumulation of substances that affect the gas consumption reaction at the negative electrode, resulting in the loss of gas consumption capacity in the later stage and an eventual increase in gas production. In this regard, the uncoated material performs better. However, a relatively thick rock-salt phase will exist on the surface of the uncoated material, and the rock-salt phase will not cause the decline of the negative electrode's consumption capacity, but will affect the electrochemical performance. Therefore, in the present application, an amorphous rock-salt phase layer that has electrochemical activity and still has the characteristics of the rock-salt phase is constructed on the high-nickel positive electrode material.

[0053] It can be understood that 0.2<d<0.6, for example 0.3, 0.4, 0.5 or a range formed by any two of them.

[0054] It can be understood that 0.2<e<0.6, for example 0.3, 0.4, 0.5 or a range formed by any two of them.

[0055] It can be understood that 0<y<0.4, for example 0.1, 0.2, 0.3 or a range formed by any two of them.

[0056] In a possible embodiment, the lithium-nickel cation mixing ratio in the inner region part is 2%-5%; the lithium-nickel cation mixing ratio in the outer region part is less than 2%. In the present application, the lithium-nickel cation mixing ratio in the outer region part is set to be less than 2%, which ensures unobstructed lithium ion diffusion channels and improves the rate performance of the material; the lithium-nickel cation mixing ratio in the inner region part is 2%-5%, which can reduce the valence state of nickel without significantly affecting the structural stability of the material.

[0057] It can be understood that the lithium-nickel cation mixing ratio in the inner region part is 2%-5%, for example 2%, 3%, 4%, 5% or a range formed by any two of them.

[0058] It can be understood that the lithium-nickel cation mixing ratio in the outer region part is less than 2%, for example 0%, 0.5%, 1%, 1.5% or a range formed by any two of them.

[0059] In one possible implementation, the absolute value of the difference between the molar percentage of manganese in the inner layer region and the molar percentage of manganese in the outer layer region is 1%-6%. The absolute value of the difference between the molar percentage of manganese in the inner layer region and the molar percentage of manganese in the outer layer region of this application is 1%-6%, ensuring that the difference in manganese content between the inner and outer layer regions is within a suitable range, thereby improving the stability of the cathode material while controlling the valence state of nickel.

[0060] It is understandable that the absolute value of the difference between the molar percentage of manganese in the inner region and the molar percentage of manganese in the outer region is 1%-6%, for example, a range consisting of 1%, 2%, 3%, 4%, 5%, 6%, or any two of these.

[0061] In one possible implementation, the molar percentage of manganese in the outer region increases gradually along the direction from the inner to the outer region of the high-nickel cathode material.

[0062] This application further defines the gradient increase of the molar percentage of manganese in the outer region, so that the change in the molar percentage of manganese in the outer region is gradient-increasing, resulting in a smooth transition of the increase in the molar percentage of manganese in the part where the outer and inner regions meet. This not only improves electrical performance, but also enhances the internal bonding strength between the outer and inner regions, thereby improving the structural stability of the cathode material.

[0063] In one possible implementation, the thickness of the amorphous rock salt phase layer is 20 nm to 40 nm. The thickness of the amorphous rock salt phase layer in this application is within the above range, which can suppress interfacial reactions on the surface of the cathode material without consuming excessive lithium, thus ensuring that lithium-nickel mixing mainly exists in the inner layer region.

[0064] It is understandable that the thickness of the amorphous rock salt phase layer is 20nm-40nm, for example, 20nm, 25nm, 30nm, 35nm, 40nm or any combination thereof.

[0065] Secondly, this application provides a method for preparing the above-mentioned high-nickel cathode material, comprising:

[0066] S1: Mix deionized water, ammonia water and alkaline solution to form a base solution. Add mixed solution A to the base solution to react and obtain reactant I. Mixed solution A includes nickel salt solution, cobalt salt solution and manganese salt solution.

[0067] S2: Ammonia water, alkaline solution and mixed solution C are passed into reactant I and reacted. After drying, the first intermediate product is obtained. The mixed solution C includes nickel salt solution, cobalt salt solution and manganese salt solution. The molar percentage of manganese in mixed solution C is greater than that in mixed solution A.

[0068] S3: The first intermediate product and the lithium source are mixed and sintered for the first time to obtain a high-nickel cathode material; wherein the amount of lithium source and the first intermediate product added satisfies the molar ratio of Li / (Ni+Co+Mn) as (0.98-1.06):1;

[0069] In step S1, this application first allows a co-precipitation reaction in mixed solution A to nucleate and grow, initially forming a hydroxide precursor (reactant I). Then, in step S2, mixed solution C is added to reactant I, with the molar percentage of manganese in mixed solution C being greater than that in mixed solution A. This allows reactant I to grow further, forming a first intermediate product where the molar percentage of manganese in the inner layer is lower than that in the outer layer. After sintering in step S3, this first intermediate product yields a high-nickel cathode material where the molar percentage of manganese in the inner layer is lower than that in the outer layer. Furthermore, by adjusting the molar ratio of Li / (Ni+Co+Mn) to (0.98-1.06):1, due to the low lithium ratio, the lithium source in the outer layer is higher than that in the inner layer during sintering. This results in a relatively lithium-deficient inner layer, meaning there are more lithium vacancies in the inner layer, thus achieving a higher lithium-nickel mixing rate in the inner layer than in the outer layer.

[0070] It is understandable that the molar ratio of Li / (Ni+Co+Mn) is (0.98-1.06):1, for example, 0.98:1, 0.99:1, 1:1, 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1 or any combination thereof.

[0071] In one possible implementation, the first sintering is carried out in an oxygen-containing atmosphere, the temperature of the first sintering is 700-900℃, and the time of the first sintering is 10-20h.

[0072] The first sintering within the aforementioned temperature range allows the material to finally form a high-nickel cathode material, resulting in a lithium-nickel mixing ratio of 2%-5% in the inner layer and less than 2% in the outer layer. If the first sintering temperature is too high, lithium will volatilize, increasing lithium vacancies and consequently leading to excessively high lithium-nickel mixing ratios in both the inner and outer layers.

[0073] Understandably, the temperature of the first sintering is 700-900℃, for example, 700℃, 720℃, 740℃, 760℃, 780℃, 800℃, 820℃, 840℃, 860℃, 880℃, 900℃ or any combination thereof.

[0074] It is understood that the first sintering time is 10-20 hours, for example, a range of 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, or any combination thereof. In one possible implementation, S3 includes:

[0075] S31: The first intermediate product is impregnated in the mixed solution D and dried to obtain the second intermediate product; wherein, the mixed solution D includes a complexing agent solution, a manganese salt solution, a salt solution containing element M and a lithium source, and M includes at least one element selected from Nb, Ti, Ta and Mo;

[0076] S32: The second intermediate product and the lithium source are mixed and sintered in a second stage to obtain a high-nickel cathode material; wherein the amount of lithium source and the second intermediate product added satisfies the molar ratio of Li / (Ni+Co+Mn) as (0.98-1.06):1; the second sintering includes a first stage sintering and a second stage sintering. The first stage sintering is carried out in an inert atmosphere at a temperature of 400-600℃ for 3-5 hours; the second stage sintering is carried out in an oxygen-containing atmosphere at a temperature of 700-900℃ for 10-20 hours.

[0077] This application obtains an amorphous rock salt phase layer on the surface by impregnating a first intermediate product in a mixed solution D, mixing it with a lithium source, and then sintering it. Furthermore, the formation of the amorphous rock salt phase layer consumes a portion of the lithium source, increasing the relative lithium deficiency in the inner region and promoting a higher lithium-nickel mixing rate in the inner region compared to the outer region.

[0078] The specific second sintering process includes a first-stage sintering and a second-stage sintering. The first-stage sintering is performed at a low temperature in an inert atmosphere, resulting in the formation of an amorphous rock salt phase layer on the material surface. The second-stage sintering is performed at a high temperature, causing the material to finally form a high-nickel cathode material, with a lithium-nickel mixing rate of 2%-5% in the inner layer and less than 2% in the outer layer. If the temperature of the second-stage sintering is too high, lithium will volatilize, increasing lithium vacancies and consequently leading to excessively high lithium-nickel mixing rates in both the inner and outer layers.

[0079] It is understandable that the temperature of the first-stage sintering is 400-600°C, for example, 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C or a range formed by any two thereof.

[0080] It is understandable that the time of the first-stage sintering is 3-5h, for example, 3h, 4h, 5h or a range formed by any two thereof.

[0081] It is understandable that the temperature of the second-stage sintering is 700-900°C, for example, 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C, 900°C or a range formed by any two thereof.

[0082] It is understandable that the time of the second-stage sintering is 10-20h, for example, 10h, 12h, 14h, 16h, 18h, 20h or a range formed by any two thereof.

[0083] In a possible embodiment, the mixed solution C includes a mixed solution A1 and a solution B, the mixed solution A1 includes a nickel salt solution, a cobalt salt solution and a manganese salt solution, and the solution B includes a manganese salt solution; when the mixed solution C is introduced into the reactant I for reaction, the introduction flow rate of the solution B in the mixed solution C is increased at set intervals, the set time is 1-3 hours, the mole percentage of manganese element in the mixed solution C is a, and the mole percentage of manganese element in the mixed solution A is b, where 0% < a-b ≤ 10%.

[0084] It is understandable that when the mixed solution C is introduced into the reactant I for reaction, the introduction flow rate of the solution B in the mixed solution C is increased at set intervals, and 0% < a-b ≤ 10% is controlled, so that the absolute value of the difference between the mole percentage of manganese element in the inner region part and the mole percentage of manganese element in the outer region part is 1%-6%.

[0085] It is understandable that the set time is 1-3 hours, for example, 1 hour, 2 hours, 3 hours or a range formed by any two thereof.

[0086] It is understandable that 0% < a-b ≤ 10%, for example, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range formed by any two thereof.

[0087] In a possible embodiment, the D of reactant I v 50 is 1.5-4μm.

[0088] In a possible embodiment, the D of the first intermediate product v50 is 3-8μm.

[0089] It is understandable that the D of reactant I v 50 is 2-4μm, for example, a range of 2μm, 3μm, 4μm or any two of them.

[0090] It is understandable that the first intermediate product D v 50 is 6-8μm, for example, a range of 6μm, 7μm, 8μm or any two of them.

[0091] In one possible implementation, in steps S1 and S2, the concentration of ammonia water is independently 9-11 mol / L.

[0092] In one possible implementation, in steps S1 and S2, the concentration of alkali in the alkaline solution is independently 8-9 mol / L.

[0093] In one possible implementation, in steps S1 and S2, the alkaline solution independently comprises an aqueous solution of NaOH.

[0094] In one possible implementation, the reaction temperature in step S2 is 50-70°C.

[0095] In one possible implementation, in step S2, when ammonia, alkaline solution and mixed solution C are introduced into reactant I for reaction, the concentration of ammonia is controlled to be 8-9 g / L and the pH value is 10-12.

[0096] In one possible implementation, in mixed solution A and mixed solution A1, the molar concentration of nickel salt in the nickel salt solution is independently 1-1.8 mol / L.

[0097] In one possible implementation, in mixed solution A and mixed solution A1, the nickel salt in the nickel salt solution independently includes at least one of nickel sulfate and nickel nitrate.

[0098] In one possible implementation, in mixed solution A and mixed solution A1, the molar concentration of cobalt salt in the cobalt salt solution is independently 0.1-0.4 mol / L.

[0099] In one possible implementation, in mixed solution A and mixed solution A1, the cobalt salt in the cobalt salt solution independently includes at least one of cobalt sulfate and cobalt nitrate.

[0100] In one possible implementation, the manganese salt concentration in the manganese salt solution in mixed solution A, mixed solution A1, and solution B is independently 0.1-0.8 mol / L.

[0101] In one possible implementation, in mixed solution A, mixed solution A1, and solution B, the manganese salt in the manganese salt solution independently includes at least one of manganese sulfate and manganese nitrate.

[0102] In one possible implementation, the base liquid is stirred while being formed, with the stirring speed being 400-600 rpm.

[0103] In one possible implementation, the lithium source in steps S3, S31 and S32 each independently includes at least one of lithium hydroxide, lithium carbonate and lithium nitrate.

[0104] In one possible implementation, in step S31, the complexing agent in the complexing agent solution includes citric acid monohydrate.

[0105] In one possible implementation, in step S31, the manganese salt in the manganese salt solution includes manganese acetate tetrahydrate.

[0106] In one possible implementation, in step S31, the salt containing element M in the salt solution containing element M includes at least one of oxalate of element M, nitrate of element M, carbonate of element M, and sulfate of element M.

[0107] Thirdly, this application provides a positive electrode sheet, including the aforementioned high-nickel positive electrode material.

[0108] The positive electrode sheet of this application specifically includes a positive current collector and a positive active layer formed of high-nickel positive electrode material disposed on the surface of the positive current collector.

[0109] In the specific preparation of the positive electrode sheet, for example, the high-nickel positive electrode material of the application can be dispersed with the conductive agent and binder in an appropriate amount of N-methylpyrrolidone (NMP) solvent, and thoroughly stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is uniformly coated on the positive electrode current collector, and after drying, rolling and cutting, the positive electrode sheet is obtained.

[0110] In one specific embodiment, the positive electrode active layer comprises, by weight percentage, 70-99 wt% high-nickel positive electrode material, 0.5-15 wt% conductive agent, and 0.5-15 wt% binder; more specifically, it comprises 80-98 wt% high-nickel positive electrode material, 1-10 wt% conductive agent, and 1-10 wt% binder.

[0111] The positive current collector can be made of at least one of aluminum foil or nickel foil; the conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber; and the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, and polyurethane.

[0112] Fourthly, this application provides a battery including the aforementioned positive electrode.

[0113] This application does not strictly limit the negative electrode active material in the negative electrode sheet. It can be at least one of the negative electrode active materials commonly used in lithium-ion batteries, such as graphite, hard carbon, soft carbon, mesophase carbon microspheres, silicon-based negative electrode materials (mainly including silicon suboxide and silicon-carbon negative electrode), and tin-based negative electrode materials (mainly including tin and tin alloy).

[0114] This application does not strictly limit the choice of electrolyte, which may include one or more solvents commonly used in lithium-ion battery electrolytes, as well as lithium salts commonly used in lithium-ion electrolytes. For example, the solvent may be ethylene carbonate, propylene carbonate, butene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, methyl ethyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, γ-butyrolactone, etc.; the lithium salt may be one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0115] This application does not strictly limit the choice of separator material. It can be one of the separator materials commonly used in lithium-ion batteries, such as polypropylene separator (PP), polyethylene separator (PE), polypropylene / polyethylene double-layer composite membrane (PP / PE), polyimide electrospun separator (PI), polypropylene / polyethylene / polypropylene triple-layer composite membrane (PP / PE / PP), cellulose nonwoven separator, and separator with ceramic coating.

[0116] In battery manufacturing, the positive electrode, separator, and negative electrode are wound or stacked to obtain a bare battery, which is then packaged into a pre-stamped aluminum-plastic film bag or steel casing. After the packaged battery is dried at 85°C, the electrolyte is injected into the dried battery. The battery undergoes resting, formation, and secondary sealing to complete battery manufacturing.

[0117] The technical solution of this application and how the technical solution of this application solves the above-mentioned technical problems are described in detail below with specific embodiments. These specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described again in some embodiments. The embodiments of this application will now be described with reference to the accompanying drawings.

[0118] Example 1

[0119] The preparation method of the high-nickel cathode material in this embodiment is as follows:

[0120] S1: Using the continuous co-precipitation method: Prepare mixed solution A, which includes nickel sulfate, cobalt sulfate and manganese sulfate, wherein the total concentration of nickel sulfate, cobalt sulfate and manganese sulfate in mixed solution A is 2 mol / L, and the molar ratio of nickel, cobalt and manganese is 6:1:3 (the concentrations of nickel sulfate, cobalt sulfate and manganese sulfate are 1.2 mol / L, 0.2 mol / L and 0.6 mol / L respectively). Prepare solution B containing 0.5 mol / L manganese sulfate, as well as an 8 mol / L NaOH aqueous solution and a 10 mol / L ammonia aqueous solution.

[0121] First, deionized water, ammonia, and NaOH aqueous solution are introduced into the reactor to form a base solution. The amounts of deionized water, ammonia, and NaOH aqueous solution added are such that the ammonia concentration of the base solution is 10 g / L and the pH value is 11. Then, the base solution is stirred at a speed of 500 rpm and the temperature is maintained at 60℃.

[0122] Mixed solution A was passed into the base solution at a flow rate of 60 mL / min, while maintaining an ammonia concentration of 8.5 g / L and a pH of 11. Reactant I was obtained.

[0123] S2: D of reactant I v At a flow rate of 50 to 2.5 μm, an 8 mol / L NaOH aqueous solution, a 10 mol / L ammonia aqueous solution, and a mixed solution C are introduced into reactant I for reaction (the ammonia concentration is maintained at 8.5 g / L, the pH is 11, and the reaction temperature is 60 °C). Mixed solution C includes mixed solution A1 (mixed solution A1 contains nickel sulfate, cobalt sulfate, and manganese sulfate; the total concentration of nickel sulfate, cobalt sulfate, and manganese sulfate in mixed solution A1 is 2 mol / L, the molar ratio of nickel, cobalt, and manganese is 6:1:3, and the concentrations of nickel sulfate, cobalt sulfate, and manganese sulfate are 1.2 mol / L, 0.2 mol / L, and 0.6 mol / L, respectively) and solution B. The flow rate of mixed solution A1 is adjusted to 55 mL / min, and the flow rate of solution B is 5 mL / min. Every 1 hour, the flow rate of solution B is increased by 1 mL / min, and the flow rate of mixed solution A1 is decreased by 1 mL / min. The reaction continues until D. vThe manganese content increases from 50 μm to 5 μm (during this process, the maximum molar percentage of manganese in mixed solution C and the difference between the molar percentage of manganese in mixed solution A is 6.5%), making the molar percentage of manganese in the inner region lower than that in the outer region. Then the machine is stopped, the material is discharged for aging, washed with water and dried to obtain the first intermediate product.

[0124] S3: Preparation of mixed solution D: Dissolve 8.82 g of citric acid monohydrate in 200 mL of deionized water, add 1.62 g of ammonium niobate oxalate, and add 12 mL of 30% hydrogen peroxide dropwise while stirring until the solution becomes clear. Then add 1.75 g of manganese acetate tetrahydrate and 2.32 g of lithium nitrate monohydrate, dissolve, transfer to a 2 L volumetric flask, add 500 mL of ethanol, and dilute to volume with deionized water.

[0125] S4: Impregnation and drying: Take 100g of the first intermediate product obtained in step S2 and mix it with 200mL of the mixed solution D obtained in step S3. After standing for 6 hours, dry at 80℃ for 6 hours and then vacuum dry at 120℃ for 6 hours to obtain the second intermediate product.

[0126] S5: Sintering: The second intermediate product obtained in step S4 is mixed with LiOH·H2O, with the molar ratio of Li / (Ni+Co+Mn) controlled at 1.03:1, and placed in a tube furnace. The mixture is heated to 550℃ at 3℃ / min and held for 3 hours under argon atmosphere; then switched to oxygen atmosphere and heated to 820℃ at 5℃ / min and held for 12 hours. After cooling, the high-nickel cathode material of this embodiment is obtained.

[0127] Figure 1 The image shows the EPMA diagram of the high-nickel cathode material in Example 1. Figure 2 for Figure 1 The Mn element concentration distribution map scanned along the red line profile, from... Figure 2 As can be seen from the outside to the inside, the Mn concentration in the outer region shows a gradually decreasing trend, while the Mn concentration in the inner region is almost at the same level. The manganese concentration in the outer region is higher than that in the inner region.

[0128] Figure 4 This is a TEM image of the high-nickel cathode material from Example 1. Figure 4 It can be seen that the high-nickel cathode material in this embodiment includes a high-nickel cathode material and an amorphous rock salt phase layer on the high-nickel cathode material, wherein the area indicated by the yellow arrow is the amorphous rock salt phase layer area.

[0129] Figure 6 The FIB-TEM image of the inner layer region of the high-nickel cathode material provided in Example 1 of this application shows that the observable bright spots are transition metal elements, such as Ni / CO / Mn elements. The gaps between the layers are lithium layers. Lithium is a light element, and no bright spots are observed there. Figure 6 A few bright spots can be seen in the lithium layer, which indicates that nickel has entered the lithium layer.

[0130] Example 2

[0131] The difference from Example 1 is that the molar ratio of nickel, cobalt, and manganese in mixed solution A is changed from 6:1:3 to 18:1:1 (the concentrations of nickel sulfate, cobalt sulfate, and manganese sulfate are 1.8 mol / L, 0.1 mol / L, and 0.1 mol / L, respectively). The D of reactant I... v At a concentration between 50 and 1.5 μm, an 8 mol / L NaOH aqueous solution, a 10 mol / L ammonia aqueous solution, and a mixed solution C were introduced into reactant I for reaction (the ammonia concentration was maintained at 8.5 g / L, the pH at 11, and the reaction temperature at 60 °C). Mixed solution C consisted of mixed solution A1 and solution B. The flow rate of mixed solution A1 was adjusted to 58 mL / min, and the flow rate of solution B was adjusted to 2 mL / min. Every 3 hours, the flow rate of solution B was increased by 1 mL / min, while the flow rate of mixed solution A1 remained constant (during this process, the difference between the maximum molar percentage of manganese in mixed solution C and the molar percentage of manganese in mixed solution A was 1.6%). The reaction continued until the first intermediate product D was obtained. v The thickness increased from 50 to 3 μm. The molar ratio of Li / (Ni+Co+Mn) was controlled at 1.04:1. Mixed solution A1 included nickel sulfate, cobalt sulfate, and manganese sulfate. The total concentration of nickel sulfate, cobalt sulfate, and manganese sulfate in mixed solution A1 was 2 mol / L, and the molar ratio of nickel, cobalt, and manganese was 18:1:1 (the concentrations of nickel sulfate, cobalt sulfate, and manganese sulfate were 1.8 mol / L, 0.1 mol / L, and 0.1 mol / L, respectively).

[0132] Meanwhile, in step S5, the temperature is raised to 400°C at 3°C / min and held for 5 hours under argon; then switched to oxygen and raised to 700°C at 5°C / min and held for 20 hours. After cooling, the high-nickel cathode material of this embodiment is obtained.

[0133] Example 3

[0134] The difference from Example 1 is that the molar ratio of nickel, cobalt, and manganese in mixed solution A was changed from 6:1:3 to 12:1:7 (the concentrations of nickel sulfate, cobalt sulfate, and manganese sulfate were 1.2 mol / L, 0.1 mol / L, and 0.7 mol / L, respectively). The flow rate of solution B was increased by 2 ml / min every hour, while the flow rate of mixed solution A1 remained unchanged (during this process, the difference between the maximum molar percentage of manganese in mixed solution C and the molar percentage of manganese in mixed solution A was 10%). The D of reactant I... v 50 is 3.5 μm, the first intermediate product D v50 is 7μm, and the molar ratio of Li / (Ni+Co+Mn) is controlled at 1.0:1.

[0135] Meanwhile, in step S5, the temperature is raised to 600°C at 3°C / min and held for 3 hours under argon; then switched to oxygen and raised to 900°C at 5°C / min and held for 10 hours. After cooling, the high-nickel cathode material of this embodiment is obtained.

[0136] Example 4

[0137] The difference from Example 1 is that the preparation method for mixed solution D is changed to dissolving 7.77 g of citric acid in a 500 mL beaker by adding approximately 200 mL of deionized water and stirring. Approximately 2.89 g of weighed tantalum oxalate powder is then slowly and gradually added to the citric acid solution while continuously stirring. In a fume hood, 12 mL of 30% hydrogen peroxide is slowly added dropwise. Once the solution becomes completely clear, 1.52 g of manganese acetate and 1.75 g of lithium nitrate are added sequentially, stirring until completely dissolved. The solution is then transferred to a 2 L volumetric flask and brought to volume.

[0138] Example 5

[0139] The difference from Example 1 is that the content of citric acid monohydrate is increased to 15g, niobium oxalate is increased to 2.43g, hydrogen peroxide is increased to 18ml, manganese acetate tetrahydrate is adjusted to 2.625g, and lithium nitrate monohydrate is adjusted to 3.48g, while the specific steps remain the same.

[0140] Example 6

[0141] The difference from Example 1 is that the molar ratio of Li / (Ni+Co+Mn) is controlled at 1.0:1.

[0142] Example 7

[0143] The difference from Example 1 is that the molar ratio of Li / (Ni+Co+Mn) is controlled at 1.04:1.

[0144] Example 8

[0145] The difference from Example 1 is that the set time was adjusted to 30 minutes (during which the maximum molar percentage of manganese in mixed solution C and the difference between the molar percentage of manganese in mixed solution A was 14%).

[0146] Example 9

[0147] The difference from Example 1 is that the set time is adjusted to 4 hours (during which the maximum molar percentage of manganese in mixed solution C and the difference between the molar percentage of manganese in mixed solution A is 2%).

[0148] Example 10

[0149] The difference from Example 1 is that steps S3 and S4 are omitted, and the first intermediate product obtained in S2 is directly mixed with LiOH·H2O, followed by subsequent sintering in S5.

[0150] Example 11

[0151] The difference from Example 1 is that in the sintering of S5, the temperature was raised to 550°C at 3°C / min and held for 3 hours under argon; then the temperature was switched to oxygen and raised to 950°C at 5°C / min and held for 12 hours. After cooling, the high-nickel cathode material of this example was obtained.

[0152] Example 12

[0153] The difference from Example 1 is that in S2: the D of reactant I v At a velocity of 50 to 2.5 μm, an 8 mol / L NaOH aqueous solution, a 10 mol / L ammonia aqueous solution, and a mixed solution C are introduced into reactant I to react (the ammonia concentration is maintained at 8.5 g / L, the pH value is 11, and the reaction temperature is 60 °C). Mixed solution C contains nickel sulfate, cobalt sulfate, and manganese sulfate, with a total concentration of 2 mol / L. The molar ratio of nickel, cobalt, and manganese is 5.44:0.91:3.65, and the molar concentrations of nickel sulfate, cobalt sulfate, and manganese sulfate are 1.088 mol / L, 0.182 mol / L, and 0.7 mol / L, respectively (i.e., the difference between the molar percentage of manganese in mixed solution C and the molar percentage of manganese in mixed solution A is 6.5%). The reaction continues until D. v The material grows to 5μm, then the machine is stopped, the material is discharged for aging, washed with water and dried to obtain the first intermediate product.

[0154] Example 13

[0155] The difference from Example 1 is that the molar ratio of Li / (Ni+Co+Mn) is controlled at 1.06:1.

[0156] Example 14

[0157] The difference from Example 1 is that the molar ratio of Li / (Ni+Co+Mn) is controlled at 0.98:1.

[0158] Comparative Example 1

[0159] The difference from Example 1 is that the molar ratio of Li / (Ni+Co+Mn) is controlled at 1.1:1.

[0160] Comparative Example 2

[0161] The difference from Example 1 is that in step S2, a mixed solution C is introduced into reactant I for reaction. The mixed solution C only includes mixed solution A, that is, solution B is not introduced, and solution A is kept at a constant flow rate of 60 ml / min (during this process, the difference between the maximum molar percentage of manganese in mixed solution C and the molar percentage of manganese in mixed solution A is 0%).

[0162] Application examples

[0163] 1) Battery test example:

[0164] The high-nickel cathode materials obtained in the above embodiments and comparative examples were assembled into batteries. The specific battery preparation method is as follows: the mass ratio of the cathode slurry was high-nickel cathode material: SP:PVDF = 94.5:3:2.5, and the solvent was NMP. The solid content of the cathode slurry was 45%. The cathode slurry was stirred using a dual planetary mixer and then coated with a coating surface density of 15 mg / cm³. 2 The compaction density is 3.3 g / cm³. 3 The corresponding negative electrode is graphite, with a mass ratio of graphite:SP:SBR:CMC = 95.5:1:2:1.5, and an areal density of 12 mg / cm³. 2 The compaction density is 1.5 g / cm³. 3 The separator is a PP separator. The positive electrode, negative electrode, and separator are wound and then injected with electrolyte for encapsulation. The electrolyte composition is 1M LiPF6 dispersed in a mixture of EC, EMC, and DEC, with a mass ratio of EC, EMC, and DEC of 1:1:1. After encapsulation, the battery is allowed to stand at 45 degrees Celsius for 12 hours before formation. The formation voltage range is 2.8-4.25V (positive electrode NCM811), and the formation voltage range for NCM613 is 2.8-4.4V. The formation current rate is 0.1C, and the cycle time is 2 cycles. Figure 5 The DQ / DV curves of the batteries in Example 1, Comparative Examples 1 and 2 after two cycles in this step are shown. The batteries are then charged to 3.85V and placed in a 45°C oven for 24 hours to facilitate more stable SEI formation. The gas bags are then removed by double sealing to obtain the battery to be tested.

[0165] The batteries obtained from the various embodiments and comparative examples were subjected to the following tests:

[0166] Gas production test: The batteries obtained from each embodiment and comparative example were charged to the upper limit voltage using constant current and constant voltage (4.25V for NCM811 and 4.4V for NCM613), with a constant current rate of 1C and a constant voltage cutoff current of 0.05C. The batteries were then placed in an explosion-proof cabinet, heated to 70°C, and stored for 42 days. Every 7 days, the batteries were taken out and charged to 4.4V using the same process. The difference between the battery volume after 42 days of storage and the battery volume before storage was measured and calculated to obtain the gas production.

[0167] 10C discharge rate cycle test: After charging at a constant current and constant voltage of 5C, discharge at a 10C rate, and then rest for 5 minutes. This is one cycle. Repeat the above steps 20 times. The capacity retention rate is the discharge capacity of the 20th cycle / the discharge capacity of the 2nd cycle * 100%.

[0168] 2) Cathode material test example:

[0169] XRD total lithium-nickel mixing ratio test of high-nickel cathode material: calculation of peak intensity ratio of I(003) / I(104).

[0170] Lithium-nickel mixing ratio in the inner layer region: The lithium-nickel mixing ratio in the inner layer region was tested using FIB-TEM: High-nickel cathode material was fixed on a TEM-specific grid, target particles were located in SEM mode, and a platinum or tungsten protective layer was deposited on its surface to protect the original surface structure of the sample during subsequent ion beam cutting; using a high-energy gallium ion beam, the target region was cut into a thin sheet approximately 10 micrometers thick by a "grooving" method. A lower-energy ion beam was used to thin the sheet to approximately 100 nanometers, making it transparent to the electron beam for TEM observation; the thinned sheet was then transferred and welded to a TEM copper grid using a nanorobotics. Finally, an ion beam with extremely low voltage and current was used for final cleaning of the sheet surface to remove any amorphous layers that may have been introduced during the thinning process, obtaining an atomically smooth surface. Subsequently, high-angle annular dark-field imaging (HAADF-STEM) was performed under aberration-corrected transmission electron microscopy. On the atomic-resolution HAADF-STEM image, the average brightness of the lithium layer and transition metal layer sites in the granular region of the inner layer was measured. The inclusion of nickel atoms in the lithium layer leads to an increase in the brightness of that layer. By comparing the brightness with that of a perfectly unmixed structure, the proportion of nickel in the lithium layer can be quantitatively calculated. The lithium-nickel mixing rate in the inner layer region was thus obtained.

[0171] The lithium-nickel mixing rate in the outer region is calculated by combining the total mixing rate obtained from XRD testing and the internal mixing rate obtained from FIB-TEM testing in the outer region. Specifically, the mixing rate of the outer region is calculated based on the volume ratio of the inner and outer regions and the mixing rate of the inner region / the total mixing rate.

[0172] Thickness test of amorphous rock salt phase layer: The thickness was obtained by FIB-TEM test. The sample preparation method was the same as the FIB-TEM sample preparation method described above. A region of about 100 nm on the particle surface was selected. The diffraction pattern was observed by selected area electron diffraction to distinguish the structure of amorphous rock salt phase. The thickness of amorphous rock salt phase was obtained according to the position of the diffraction pattern change.

[0173] Composition of amorphous rock salt phase: determined by XPS analysis. Specific testing method: magnesium target was used. XPS fine spectral parameters were: POWER 225, PE 40, step size 0.1, Dwell time 300ms. The tested elements were those contained within the amorphous rock salt phase, and the etching depth was 60nm.

[0174] Chemical testing of high-nickel cathode materials: ICP was used to test high-nickel cathode materials.

[0175] Molar percentage of manganese in the inner layer region: A profile sample was prepared using argon ion polishing and tested using EPMA (accelerating voltage 15kV / beam current 150nA / spot size min). Five particles were randomly selected in the profile region for line testing to obtain the Mn signal intensity change from the particle surface to the particle center. Based on this line test, the molar amount of Mn in the inner and outer layers of each particle was calculated, and then the average molar amount of Mn in the inner and outer layers of the five particles was obtained. 2g of material was weighed for ICP testing to obtain the total molar percentage of each element in the material. The molar percentage of Mn in the inner and outer layers was calculated based on the average molar amount of Mn in the inner and outer layers and the average total molar amount of nickel, cobalt, and manganese in the cathode material.

[0176] The test results are shown in Tables 1-2.

[0177] Table 1

[0178]

[0179] Table 2

[0180]

[0181] Figure 3 XPS valence state test images of the material surfaces in Examples 1, 1, and 2 are shown below. Figure 3 It can be seen that the average valence state of nickel on the surface of the cathode material in Example 1 is relatively low. Figure 5The DQ / DV curves of the batteries in Example 1, Comparative Examples 1 and 2 during the charge-discharge cycle process show that the lower the degree of lithium-nickel mixing, such as Comparative Example 1, the lower the peak voltage at the high voltage end, indicating that its delithiation energy barrier is lower and delithiation is easier, but the average valence state is increased, resulting in an increase in the final gas production.

[0182] As can be seen from Table 1-2, compared with Example 1 and Example 8, due to the shorter set time, the manganese content in the outer layer of the material is higher, resulting in a higher Ni content in the outer layer. 2+ The increased concentration of lithium and nickel leads to a higher degree of lithium-nickel mixing, resulting in slightly poorer rate performance.

[0183] Comparing Example 1 and Example 9, due to the longer setting time, the manganese content in the outer layer region of the material is similar to that in the inner layer region. However, appropriately increasing the Mn content on the surface can form a specific crystal structure (such as twin boundaries), providing an efficient diffusion channel for lithium ions, thereby improving the rate performance. Therefore, Example 9 ultimately resulted in slightly worse rate performance.

[0184] Compared with Example 1 and Example 10, the lack of amorphous rock salt phase resulted in a decrease in rate performance and an increase in gas production.

[0185] In Comparative Examples 1 and 11, the excessively high sintering temperature led to an increase in the lithium-nickel mixing rate between the inner and outer layers. The significantly increased lithium-nickel mixing rate on the surface promoted the formation of an electrochemically inert rock salt phase, resulting in a decrease in the rate performance of the final material.

[0186] Comparing Example 1 and Example 12, the capacity and rate performance decreased because the molar percentage of manganese in the mixed solution C in step S2 did not increase in a gradient.

[0187] Comparing Example 1 and Example 13, the increased lithium ratio resulted in a higher lithium content and fewer lithium vacancies in the lithium layer of the material during the synthesis process, leading to a decrease in the lithium-nickel mixing ratio, an increase in the average valence state of nickel, and ultimately a decrease in gas production performance.

[0188] Comparing Example 1 and Example 14, the increased lithium ratio leads to a decrease in the lithium layer of the material during synthesis, resulting in more lithium vacancies and ultimately an increased lithium-nickel mixing rate, which in turn reduces the rate performance of the material.

[0189] Compared with Example 1, the molar ratio of Li / (Ni+Co+Mn) was too large, which led to a decrease in the lithium-nickel mixture in the comparative example, resulting in an increase in the average valence state of nickel and an increase in gas production, i.e., a higher interfacial oxidation activity.

[0190] Compared with Example 1 and Comparative Example 2, mixed solution C only includes mixed solution A, that is, solution B is not introduced, which results in the manganese content of the inner and outer regions being basically the same, which leads to an increase in the structural stability of the material and the average valence state of nickel. Therefore, the rate performance is slightly worse and the gas production is increased.

[0191] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.

Claims

1. A high-nickel cathode material, characterized in that, The chemical formula of the high-nickel cathode material includes Li 1-x Ni a Co b Mn c O2, where 0.01≤x≤0.05, 0.55≤a≤0.9, 0≤b≤0.2, 0≤c≤0.4, 2.1≤2a+3b+4c≤2.85; The high-nickel cathode material includes an inner layer region and an outer layer region, the outer layer region covering the outer surface of the inner layer region, and the lithium-nickel mixing ratio in the inner layer region is higher than that in the outer layer region; wherein, the lithium-nickel mixing ratio is the proportion of Ni atoms occupying Li sites; The molar percentage of manganese in the inner layer region is lower than that in the outer layer region; the molar percentage of manganese in the inner layer region is the percentage of the molar amount of manganese in the inner layer region relative to the total molar amount of nickel, cobalt, and manganese in the high-nickel cathode material; the molar percentage of manganese in the outer layer region is the percentage of the molar amount of manganese in the outer layer region relative to the total molar amount of nickel, cobalt, and manganese in the high-nickel cathode material. The inner layer region is the region formed from the geometric center of the high-nickel cathode material to a region of R / 2; the outer layer region is the region formed from R / 2 to R; where R is the radius of the high-nickel cathode material.

2. The high-nickel cathode material according to claim 1, characterized in that, The surface of the high-nickel cathode material is coated with an amorphous rock salt phase layer. The chemical formula of the amorphous rock-salt phase layer includes Li 1+y M d Mn e O Z , where 0.2<d<0.6, 0.2<e<0.6, 0<y<0.4, M includes at least one element selected from Nb, Ti, Ta and Mo, and 1+y+d*(valence state of element M)+e*3=2Z.

3. The high-nickel cathode material according to claim 1 or 2, characterized in that, The lithium-nickel mixing rate in the inner layer region is 2%-5%; the lithium-nickel mixing rate in the outer layer region is less than 2%.

4. The high-nickel cathode material according to claim 1 or 2, characterized in that, The absolute value of the difference between the molar percentage of manganese in the inner layer region and the molar percentage of manganese in the outer layer region is 1%-6%.

5. The high-nickel cathode material according to claim 1 or 2, characterized in that, Along the direction from the inner layer region to the outer layer region of the high-nickel cathode material, the molar percentage of manganese in the outer layer region gradually increases.

6. The high-nickel cathode material according to claim 2, characterized in that, The thickness of the amorphous rock salt phase layer is 20nm-40nm.

7. A method for preparing a high-nickel cathode material according to any one of claims 1-6, characterized in that, The method includes: S1: Mix deionized water, ammonia water and alkaline solution to form a base solution. Add mixed solution A to the base solution to react and obtain reactant I. Mixed solution A includes nickel salt solution, cobalt salt solution and manganese salt solution. S2: Ammonia water, alkaline solution and mixed solution C are passed into reactant I and reacted. After drying, a first intermediate product is obtained. The mixed solution C includes nickel salt solution, cobalt salt solution and manganese salt solution. The molar percentage of manganese in the mixed solution C is greater than the molar percentage of manganese in the mixed solution A. S3: The first intermediate product and the lithium source are mixed and sintered for the first time to obtain the high-nickel cathode material; wherein the amount of lithium source and the first intermediate product added satisfies the molar ratio of Li / (Ni+Co+Mn) as (0.98-1.06):

1.

8. The preparation method according to claim 7, characterized in that, The first sintering is carried out in an oxygen-containing atmosphere, the temperature of the first sintering is 700-900℃, and the time of the first sintering is 10-20h.

9. The preparation method according to claim 7, characterized in that, S3 includes: S31: The first intermediate product is impregnated in the mixed solution D and dried to obtain the second intermediate product; wherein, the mixed solution D includes a complexing agent solution, a manganese salt solution, a salt solution containing element M and a lithium source, and M includes at least one element selected from Nb, Ti, Ta and Mo; S32: The high-nickel cathode material is obtained by mixing the second intermediate product and the lithium source and performing a second sintering; wherein the amount of lithium source and the second intermediate product added satisfies the molar ratio of Li / (Ni+Co+Mn) as (0.98-1.06):1; the second sintering includes a first stage sintering and a second stage sintering, wherein the first stage sintering is carried out in an inert atmosphere, the temperature of the first stage sintering is 400-600℃, and the time of the first stage sintering is 3-5h; the second stage sintering is carried out in an oxygen-containing atmosphere, the temperature of the second stage sintering is 700-900℃, and the time of the second stage sintering is 10-20h.

10. The preparation method according to any one of claims 7-9, characterized in that, The mixed solution C includes mixed solution A1 and solution B. Mixed solution A1 includes nickel salt solution, cobalt salt solution and manganese salt solution. Solution B includes manganese salt solution. When reactant I is introduced into mixed solution C for reaction, the flow rate of solution B in mixed solution C is increased at set intervals; the set intervals are 1-3 hours, the molar percentage of manganese in mixed solution C is a, and the molar percentage of manganese in mixed solution A is b, wherein 0% <a-b≤10%。 11. A positive electrode plate, characterized in that, Including the high-nickel cathode material according to any one of claims 1-6.

12. A battery, characterized in that, Including the positive electrode sheet according to claim 11.